Scoparone Improves Nonalcoholic Steatohepatitis Through Alleviating JNK/Sab Signaling Pathway-Mediated Mitochondrial Dysfunction - Jiang, Yuwei; Xu, Jiaoya; Huang, Ping; Yang, Lili; Liu, Yang; Li, Yiping; Wang, Jue; Song, Haiyan; Zheng, Peiyong (Frontiers in Pharmacology, 2022)
The activated c-Jun N-terminal kinase (JNK) specifically combined with SH3 domain-binding protein 5 (Sab) may mediate damage to the mitochondrial respiratory chain. Whether mitochondrial dysfunction induced by the JNK/Sab signaling pathway plays a pivotal role in the lipotoxic injury of nonalcoholic steatohepatitis (NASH) remains a lack of evidence. Scoparone, a natural compound from Traditional Chinese Medicine herbs, has the potential for liver protection and lipid metabolism regulation. However, the effect of scoparone on NASH induced by a high-fat diet (HFD) as well as its underlying mechanism remains to be elucidated. The HepG2 and Huh7 cells with/without Sab-knockdown induced by palmitic acid (PA) were used to determine the role of JNK/Sab signaling in mitochondrial dysfunction and cellular lipotoxic injury. To observe the effect of scoparone on the lipotoxic injured hepatocytes, different dose of scoparone together with PA was mixed into the culture medium of HepG2 and AML12 cells to incubate for 24 h. In addition, male C57BL/6J mice were fed with an HFD for 22 weeks to induce the NASH model and were treated with scoparone for another 8 weeks to investigate its effect on NASH. Molecules related to JNK/Sab signaling, mitochondrial function, and lipotoxic injury were detected in in vitro and/or in vivo experiments. The results showed that PA-induced activation of JNK/Sab signaling was blocked by Sab knockdown in hepatocytes, which improved mitochondrial damage, oxidative stress, hepatosteatosis, cell viability, and apoptosis. Scoparone demonstrated a similar effect on the PA-induced hepatocytes as Sab knockdown. For the NASH mice, treatment with scoparone also downregulated the activation of JNK/Sab signaling, improved histopathological changes of liver tissues including mitochondrial number and morphology, lipid peroxide content, hepatosteatosis and inflammation obviously, as well as decreased the serum level of lipid and transaminases. Taken together, this study confirms that activation of the JNK/Sab signaling pathway-induced mitochondrial dysfunction plays a crucial role in the development of NASH. Scoparone can improve the lipotoxic liver injury partially by suppressing this signaling pathway, making it a potential therapeutic compound for NASH.